Effects of surface features on sulfur dioxide adsorption on calcined NiAl hydrotalcite-like compounds - Zhao, L.; Li, Xin Yong; Quan, X.; Chen, G. (2011)
The hydrotalcite-based NiAl mixed oxides were synthesized by coprecipitation and urea hydrolysis approaches and employed for SO2 removal. The samples were well characterized by inductively coupled plasma (ICP) elemental analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and N2 adsorption/desorption isotherm analyses. The acid-base properties were characterized by pyridine chemisorption and CO2 temperature- programmed desorption (TPD). The calcined NiAlO from the urea method showed excellent SO2 adsorption and its adsorption equilibrium showed a type I isotherm, which significantly improved the adsorption performance for low-concentration SO2. Both the physical structure and the acidic-basic sites were found to play important roles in the SO2 adsorption process. In situ Fourier transform infrared spectroscopy (FTIR) investigation revealed that adsorbed SO2 molecules formed surface bisulfite, sulfite, and bidentate binuclear sulfate. The mechanisms for SO 2 adsorption and transformation are discussed in detail. © 2011 American Chemical Society.